INTERAKSI SOSIAL PENGAJIAN ONLINE KITAB TURATS DALAM MEMBENTUK JIWA KEAGAMAAN MASYARAKAT DI WILAYAH BOJONEGORO - Zaini Miftah, Zaini Miftah; Fahrurrozi; Taseman (At-Tuhfah : Jurnal Studi Keislaman, 2022)
This paper reveals the dynamics of the social interaction of online recitation of the turots book in shaping the religious spirit of the community. In this online learning system, it turns out that it is still a magnet in itself in society, even with a wider reach; it can be followed by all levels of the santri community. In "Ngaji Online" it is handled by authoritative figures, so that it becomes a special attraction and will even increase enthusiasm in modern society as it is today. As a result, after attending the regular recitation of the Turots book, the community has a better change in behavior, including: commitment to religious orders and prohibitions, being active in religious activities, eager to study religious teachings, and religious teachings being used as a source of developing ideas, and tawadlu' in all fields